Performance of transgenic maize genotypes against ear caterpillars in Argentina - Barontini, Javier Miguel (2020)
Maize (Zea mays L.) is one of the most widely cultivated crops in the world and Argentina is a leading producer worldwide. Lepidopteran pests such as the fall army worm (Spodoptera frugiperda -J. E. Smith-) and the corn earworm (Helicoverpazea -Boddie-) cause ear damage, producing yield losses and facilitating the entry of pathogenic fungi such as Aspergillus flavus. Under conditions of high temperatures and drought stress,some Aspergillus strains can produce Aflatoxin B1 (AFB1), which is highly carcinogenic for humans and animals. The main aim of the current study was to determine the performance of PowerCore®, PowerCore® Ultra and Genuity® VT triple PRO®Bthybrid maize to corn ear caterpillar damage in Santiago del Estero, Argentina. Since 1990,the agricultural land area in this province has increased due to the forest clearance for agriculture. Climatic conditions in the region are favourable for aflatoxin. PowerCore® Ultra showed the highest yield and, PowerCore®registered the lowest severity of damage by corn ear caterpillar. The correlation between yield and insect damage severity was negative under the conditions evaluated.